0.019///////////////////////////////////////////////////////////////////If u dont believe use calculator
Answer:
hvhhjnblnj. hlvb/ljb/u'n
Step-by-step explanation:
Answer:
(f + g)(x) = 4x + 1
Step-by-step explanation:
Given f(x) = 3x - 1 and g(x) = x + 2, find (f + g)(x):
We can rewrite (f + g)(x) as f(x) + g(x), and solve the composite functions through addition:
f(x) + g(x) = (3x - 1) + (x + 2)
Combine like terms:
f(x) + g(x) = 3x + x + 2 - 1 = 4x + 1
Therefore, (f + g)(x) = 4x + 1.
Please mark my answers as the Brainliest if you find my explanations/solution helpful :)
I would go with
G: 4 cm
Or
J: 8 cm
Let me know if you get it correct! :)